PENGARUH MEDIA INTERAKTIF WORDWALL TERHADAP MOTIVASI BELAJAR SISWA KELAS VII PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 2 KUTAWALUYA - Jaoharoh Amani, Suci; Taufik Mustofa; M. Makbul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was conducted to examine the effect of Wordwall-based interactive learning media on the learning motivation of seventh-grade students in Islamic Religious Education and Character Education at SMP Negeri 2 Kutawaluya. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 88 students, including 45 students in the experimental group and 43 students in the control group. Data were collected through a learning motivation questionnaire based on a likert scale. The collected data were analyzed using descriptive and inferential statistics through the Mann-Whitney test. The findings revealed that prior to the treatment, there was no significant difference in learning motivation between the experimental and control groups, as indicated by an Asymp. Sig. value of 0,085 > 0,05. Following the implementation of Wordwall, the experimental group achieved an average motivation score of 83,91, while the control group obtained a score of 73,26. Furthermore, the Mann-Whitney test produced an Asymp. Sig. value of 0,000 < 0,05, indicating a statistically significant difference between the two groups. Therefore, it can be concluded that the use of Wordwall interactive learning media positively influences students' learning motivation in Islamic Religious Education and Character Education.